Prediction of 2-acetyl-1-pyrroline content in grains of Thai Jasmine rice based on planting condition, plant growth and yield component data using chemometrics - Sujitra Funsueb (2018)
© 2016 Elsevier B.V. The aim of this research was to simultaneously investigate the effects of nitrogen (N) fertilizer and salinity (NaCl) treatments on aromatic quality of Oryza sativa L. ssp. indica cv. Pathumthani 1 (PT1) rice grain. The levels of N and NaCl were designed based on a central composite design (CCD). During the cultivation, plant growth parameters such as number of tillers, plant height and root length were recorded. After the harvest, yield components including number of grains per panicle, panicle length, plant weight, shoot and root dry weights, number of panicle per plant, number of grains per plant and thousand grain weight were collected. The concentrations of 2-acetyl-1-pyrroline (2AP), a key odor-active compound, in the grains were analyzed using gas chromatography-nitrogen phosphorus detector (GC-NPD). Using partial least squares (PLS), the root mean square error of cross validation (RMSECV) value was 0.091 with the Q2value of 0.8470. Based on PLS coefficients and variable influence on projection (VIP) values, N, Na, the rice yield, the shoot dry weight and the number of tillers per plant were identified to have strong influence on the prediction of the 2AP content. The behaviors of the heavily influenced parameters were confirmed and visualized using self-organizing map (SOM).